An overview on coalitional game-theoretic approaches for resource allocation in cloud computing architectures. (1st January 2015) - Jebalia, Maha; Ben Letaïfa, Asma; Hamdi, Mohamed; Tabbane, Sami
In this paper, we will deal with resource allocation problem in cloud computing environments where users compete to have enough resources to run their applications and store their data. First, we will present an overview of the resource allocation models adopted in literature and focus essentially on game theoretic approaches. To this purpose, a set of criteria will be defined so as to assess the performance of the proposed game models with respect to cloud computing needs in terms of QoS and security. At the end of this paper, we will formalise and discuss an optimisation model for resource allocation based on a cooperative game approach where cloud providers may form a pool of resources in order to maximise their profit. We will especially focus on providing a model that compensates losses generated by the adoption of security mechanisms and maximises the overall payoff.